Tinjauan Historis dan Nilai Folosofis Lambi Tilulu Sebagai Warisan Budaya Masyarakat Boalemo - Duwi Fitri Andani; Nadira A. Jaya; Mardiyah A.S. Taulama; Rahmat Syarif F. Usman (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Lambi Tilulu is a traditional dish of the Boalemo community whose existence is increasingly threatened by shifting consumption patterns and modern culinary dominance. Gorontalo Province has a minimal number of Intangible Cultural Heritage (ICH) designations, making the urgent documentation of Lambi Tilulu crucial to prevent cultural extinction. This study aims to examine the historical and philosophical values of Lambi Tilulu as a baseline for its ICH nomination. Using a qualitative approach, data were collected through observation, in-depth interviews, documentation, and triangulation. The results show that historically, Lambi Tilulu served as a food resilience mechanism for the Boalemo community during the 1960s–1970s, rooted in banana as a strategic commodity since the 19th century. Philosophically, it represents four dimensions of local wisdom: (1) adaptability and food resilience amid limitations; (2) simplicity and agrarian self-reliance; (3) a maritime-coastal identity uniting agrarian and marine resources; and (4) egalitarianism that dismantles social stratification. In conclusion, Lambi Tilulu is not merely traditional food but a "cultural text" recording the historical trajectory, ecological adaptation, and value system of the Boalemo people. Its preservation requires systematic strategies through scientific documentation, cross-generational community involvement, digital media utilization, gastronomic tourism development, and official ICH registration.